Mapping The Intellectual Landscape Of Employee Performance And Work Motivation: A Bibliometric Analysis Of Management Research (1990–2025) - Prince Hartawan; Mauli Siagian (International Journal of Education Management and Religion, 2026)
This study maps the intellectual landscape of research on employee performance and work motivation from 1990 to 2025 through a comprehensive bibliometric analysis. Using data extracted from the Scopus database and analyzed with VOSviewer and Biblioshiny, the study identifies publication trends, key authors, influential sources, and thematic clusters that shape the evolution of this field. The analysis reveals an increasing scholarly interest in the topic, reflected in a steady growth rate of publications (0.98% annually) and a strong collaboration index (5.4 co-authors per paper). The findings highlight that motivation and employee performance remain central research themes, often interlinked with concepts such as human resource management, productivity, and job satisfaction. Thematic mapping indicates three major clusters: traditional motivation-performance theories, human capital and organizational behavior perspectives, and emerging trends in digital work environments. Despite consistent academic attention, the field shows limited theoretical innovation in recent years, underscoring the need to revisit classical frameworks in light of modern organizational dynamics. This study contributes to management scholarship by providing a structured overview of the research landscape, identifying intellectual gaps, and suggesting directions for future research on employee performance and motivation in the evolving world of work.